"I Love Paw Patrol!": Book Selection and the Allure of Popular Media Characters Among Preschoolers. Issue 2 (2nd April 2020) - Jacoby, Jennifer Wallace; Edlefsen, Karen
ABSTRACT: In this quantitative study, we report the book preferences of a diverse group of preschool children ( N = 61) from two distinct early childhood settings: an urban Head Start and a private preschool. Children participated in a book selection task and were also asked a series of questions about how and why they chose the book. Parent questionnaires were gathered to provide information on children's home language, race/ethnicity, gender, and book and media exposure. All children overwhelmingly preferred books featuring popular television characters on the cover. Gender emerged as the only relevant socio-demographic feature, with girls being more likely than boys to choose a book with a popular media character. Overall, children's book preferences were more similar than different despite the diversity of the sample. Furthermore, these results expand the notion of genre in relation to children's book choices.